Local Application of Mineral-Coated Microparticles Loaded With VEGF and BMP-2 Induces the Healing of Murine Atrophic Non-Unions - Orth, M.; Fritz, T.; Stutz, J.; Scheuer, C.; Ganse, B.; Bullinger, Y.; Lee, J. S.; Murphy, W. L.; Laschke, M. W.; Menger, M. D.; Pohlemann, T. (Frontiers in Bioengineering and Biotechnology, 2022)
Deficient angiogenesis and disturbed osteogenesis are key factors for the development of nonunions. Mineral-coated microparticles (MCM) represent a sophisticated carrier system for the delivery of vascular endothelial growth factor (VEGF) and bone morphogenetic protein (BMP)-2. In this study, we investigated whether a combination of VEGF- and BMP-2-loaded MCM (MCM+VB) with a ratio of 1:2 improves bone repair in non-unions. For this purpose, we applied MCM+VB or unloaded MCM in a murine non-union model and studied the process of bone healing by means of radiological, biomechanical, histomorphometric, immunohistochemical and Western blot techniques after 14 and 70 days. MCM-free non-unions served as controls. Bone defects treated with MCM+VB exhibited osseous bridging, an improved biomechanical stiffness, an increased bone volume within the callus including ongoing mineralization, increased vascularization, and a histologically larger total periosteal callus area consisting predominantly of osseous tissue when compared to defects of the other groups. Western blot analyses on day 14 revealed a higher expression of osteoprotegerin (OPG) and vice versa reduced expression of receptor activator of NF-κB ligand (RANKL) in bone defects treated with MCM+VB. On day 70, these defects exhibited an increased expression of erythropoietin (EPO), EPO-receptor and BMP-4. These findings indicate that the use of MCM for spatiotemporal controlled delivery of VEGF and BMP-2 shows great potential to improve bone healing in atrophic non-unions by promoting angiogenesis and osteogenesis as well as reducing early osteoclast activity.